CLINICAL CHARACTERISTICS OF CYTOMEGALOVIRUS RETINITIS IN HUMAN IMMUNODEFICIENCY VIRUS (HIV) PATIENTS UNDERGOING INTRAVITREAL GANCICLOVIR INJECTION - effendi, yulia; Widyanatha, Made Indra; Ihsan, Grimaldi; Virgana, Rova; Iskandar, Erwin; Kartasasmita, Arief S (International Journal of Retina, 2024)
Introduction: Cytomegalovirus (CMV) retinitis is the most common ocular opportunistic infection in patients with Human immunodeficiency virus (HIV). The disease is causing blindness and current management commonly characterized by delayed diagnosis and inadequate treatment. Purpose: to describe the clinical characteristic and visual outcome of CMV retinitis with HIV treated with intravitreal ganciclovir injection. Methods: This is a retrospective study included 23 patients (34 eyes) who presented with CMV Retinitis with HIV from January 2020 to July 2023 who received intravitreal ganciclovir in both the induction and maintenance phases until declared cured, characterized by lesion inactivation and CD4+ T-cell counts reaching >100/µL within period of 3 to 6 months. Data were collected including age, gender, affected eye laterality, CD4+ T-cell count at the initial visit at vitreoretinal polyclinic and the 6-month follow-up, total number of intravitreal ganciclovir injections, HAART history at the initial visit, visual acuity at the initial visit, 6-month follow-up, and systemic comorbidities. Result: The median age was 29 years old with 82,6% of them male. Bilateral lesions were observed in 60.9% of the patients. Median CD4 count initial visit was 50 with 52% below 50 cell/µL. Fifteen patients (65,2%) already treated with highly active antiretroviral therapy (HAART) before injection. Tuberculosis was the most common opportunistic infection. Mean intraviteral ganciclovir injection 9,12±3,40 in each eye. Eleven eyes (32.4%) with initial visual acuity ≤1.00 logMAR increased to 19 eyes (55.9%) at the 6-month follow-up. There were statistically significant difference between baseline visual acuity and 6-months follow up after intravitreal ganciclovir. (p= 0,008). Conclusion: Retinitis cytomegalovirus tend to have more severe clinical presentations in patients with CD4 counts below 50 cells/µL. Intravitreal ganciclovir is effective in controlling CMV retinitis.